2013
DOI: 10.3389/fpsyg.2013.00079
|View full text |Cite
|
Sign up to set email alerts
|

Personality and Personality Disorders in Urban and Rural Africa: Results from a Field Trial in Burkina Faso

Abstract: When conducting research in different cultural settings, assessing measurement equivalence is of prime importance to determine if constructs and scores can be compared across groups. Structural equivalence implies that constructs have the same meaning across groups, metric equivalence implies that the metric of the scales remains stable across groups, and full scale or scalar equivalence implies that the origin of the scales is the same across groups. Several studies have observed that the structure underlying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 46 publications
(63 reference statements)
2
19
0
1
Order By: Relevance
“…One obstacle to cross-cultural personality research is judging whether differences are genuine or instead artifacts due to methodological inconsistencies (69). For example, failures of samples in low-income countries to replicate the Big Five structure have been blamed on inconsistent response styles of participants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One obstacle to cross-cultural personality research is judging whether differences are genuine or instead artifacts due to methodological inconsistencies (69). For example, failures of samples in low-income countries to replicate the Big Five structure have been blamed on inconsistent response styles of participants.…”
Section: Discussionmentioning
confidence: 99%
“…Other findings with indigenous populations are instructive. For example, failure to demonstrate the Big Five has also been recently shown among both rural and urban Mossi in Burkina Faso (69). Among 12 isolated languages, including Maasai, Fijian, and Enga, a lexical approach documenting universal attribute concepts highlighted just two dimensions of dynamism and social self-regulation (70).…”
Section: Socioecological Complexity and Personality Diversificationmentioning
confidence: 99%
“…The Personality Disorder Questionnaire and Interview had acceptable psychometric properties in Chinese (Yang et al, 2000), and the International Personality Disorder Examination had acceptable interrater reliability and temporal stability in samples of clinical patients from cities across North America, Europe, Africa, and Asia (Loranger et al, 1994), a study that found Borderline Personality Disorder (BPD) especially prevalent. The inventory structure was also stable in a sample of French-speaking African countries, and when translated into Moor e, and administered by interview to villagers in Burkina Faso (Rossier, Ouedraogo, Dahourou, Verardi, & Meyer de Stadelhofen, 2013). Though thresholds for impairment may vary, there are surely individuals who "deviate markedly from the expectations of their culture" in every society (Tseng, 2001).…”
Section: Borderline and Other Personality Disordersmentioning
confidence: 99%
“…Furthermore, these studies should encompass this "proneness" at least to a certain extent as well, as they all sampled older adults. It seems more likely that the use of the Personality Disorders Questionnaire (PDQ-4), which has a high false positive rate [10] and cultural aspects might account for this difference, as studies show that individuals living in more traditional societies, as is Central Africa, score higher on dependent traits than those in more westernized cultures [11]. Moreover, the cognitive status might bias the judgements about PDs; interviewees might have attributed some items (incorrectly) to enduring personality patterns instead of to the person's current (cognitive) state.…”
Section: Identificationmentioning
confidence: 99%